Pemberdayaan UMKM Komunitas Jakarta Entrepreneur Tentang Inovasi Pengemasan Makanan Dan Minuman - Alda Chairani; Heny Ratnaningtyas; Pricilia Johani Sakti; Michael Khrisna Aditya; Eduard Rudolf Pangkerego (Fakultas Teknik, Universitas PGRI Banyuwangi, 2024)
Extension activities regarding food and beverage packaging aim to provide relevant knowledge and skills to MSMEs in the Jakarta Entrepreneur community in an effort to improve the quality of their products and competitiveness in the market. This extension activity is carried out through direct assistance with initial observations and evaluations to understand and improve the packaging process, counseling with presentations, and training on packaging techniques. The pre-test and post-test are used to measure changes in participants' knowledge and skills, with the aim of improving the quality of product packaging and the competitiveness of MSMEs in the market. Product packaging outreach activities for MSMEs in the Jakpreneur community succeeded in increasing participants' understanding of the importance of good packaging. Through mentoring, counseling, outreach and consultation, participants now understand packaging as product protection and an important information medium. In order for this understanding to continue, MSME players are advised to take part in further training and ongoing assistance, as well as involving the government and industry associations to ensure compliance with packaging standards.